2017
DOI: 10.21470/1678-9741-2017-0072
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Nosocomial Infections in Pediatric Patients with Extracorporeal Membrane Oxygenation Support

Abstract: IntroductionExtracorporeal membrane oxygenation (ECMO) has become a standard technique over the past few decades in intensive care unit (ICU).ObjectiveA review of pediatric patients who received ECMO support in the pediatric cardiac ICU was conducted to determine the incidence, risk factors and causal organisms related to acquired infections and assess the survival rates of ECMO patients with nosocomial infections.MethodsSixty-six patients who received ECMO support in the pediatric cardiac ICU between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 27 publications
(39 reference statements)
4
14
3
2
Order By: Relevance
“…Our results showed that 28% of patients developed at least one episode of NI during ECMO, which was consistent with the previous results of 20–45% for pediatric and adults patients ( 19 21 , 23 ). The incidence of NI in this study was 47.6 cases per 1,000 ECMO days, which was in accordance with the previously reported values of between 10 and 116.2 per 1,000 ECMO days ( 19 21 , 23 , 24 ). The prolonged ECMO duration, ICU duration, and peritoneal dialysis were independent factors associated with the development of NI during ECMO.…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that 28% of patients developed at least one episode of NI during ECMO, which was consistent with the previous results of 20–45% for pediatric and adults patients ( 19 21 , 23 ). The incidence of NI in this study was 47.6 cases per 1,000 ECMO days, which was in accordance with the previously reported values of between 10 and 116.2 per 1,000 ECMO days ( 19 21 , 23 , 24 ). The prolonged ECMO duration, ICU duration, and peritoneal dialysis were independent factors associated with the development of NI during ECMO.…”
Section: Discussionsupporting
confidence: 93%
“…Septicemia was the leading cause of death in our patients. The most prevalent pathogen was bacteria, particularly those with extensive drug resistance, which was consistent with other studies ( 26 , 27 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, this study did not evaluate the concentrations of NaCl in the specimens (34). Ayyıldız et al indicated that 8.8% of the patients in the ICU had A. baumannii when they were using extracorporeal membrane oxygenation (ECMO) as a standard technique to support temporary cardiovascular and respiratory aid to the patients in ICU (35). Moreover, Lee et al showed that 7.5% of the patients were colonized with MDR A. baumannii.…”
Section: Discussionmentioning
confidence: 91%